Law Enforcement Criminal Acts of Corruption in The Perspective of Human Rights - Ansori Ansori (Rechtsidee, 2015)
The overall impact of the acts of corruption according to criminology science, certainly can happen due to two things, namely the first due to the intent or in the science of law is referred to as the evil inner attitude (Mens Rea), and the second because of an opportunity to do evil deeds (Actus Reus). Actus Reus and Mens Rea are an essential element of a crime. The eradication of corruption and the efforts of promoting and fulfilling human rights are not simply left to the elite rulers, because frequently they are more corrupt and oppressive. Corruption eradication efforts can be maximized, while a simultaneous awareness of the Government and people of the importance of protecting, fulfill, maintain, and promote human rights, then it is not impossible that Indonesia becomes a prosperous country, given the authorized capital of development in this country has been in existence since ancient times which is a priceless grace of God Almighty. How To Cite: Ansori, A. (2015). Law Enforcement Criminal Acts of Corruption in The Perspective of Human Rights. Rechtsidee, 2(2), 79-108. doi:http://dx.doi.org/10.21070/jihr.v2i2.83